Geopolitical determinism: The origins of the Iran-Iraq war - Karsh, Efrayim (The Middle East journal, 1990)
In the case of the Iran-Iraq war, the general cause is often attributed to the ethnic and religious divide that has separated Arabs and Persians, Shi'i and Sunni Muslims since at least the seventh century. This article offers an alternative explanation. It argues that geopolitics is the most important single factor that has influenced Iranian-Iraqi relations for generations and, in consequence, accounts for the outbreak of the war. More concretely, the war began because the weaker state, Iraq, attempted to resist the hegemonic aspirations of its stronger neighbor, Iran, to reshape the regional status quo according to its own image. (DÜI-Hns)